Problems of Dayah Economic Development in Bireuen County (Using QSPM SWOT Analysis) - Bismi Purnama; Marliyah Marliyah; Kamilah Kamilah (Journal Research of Social Science, Economics, and Management, 2022)
Dayah, the oldest Islamic educational institution in Aceh, has contributed to the development of human resources (HR). Initially, learning activities took place only in frames, which was an important focus in the eyes of the research community. Dayah education can be said to be at the same level as Madrasah Aliyah (MA) or Senior High School (SLTA) while recitation in meunasah is equivalent to Tsanawiyah or Junior High School (SLTP). This study aims to find out how the priority strategy in the economic development of dayah in Bireuen district by presenting the internal and external circumstances that have been carried out so far. Then in addition, the researcher also explained some of the urgency of handling that needs to be applied so that the economic development of dayah in birueun district can be more targeted. The method used is a qualitative method using SWOT and QSPM analysis. The number of respondents who filled out the questionnaire was 9 respondents from dayah management and 5 respondents from expert experts, respectively. Based on the results of the SWOT analysis, the quadrants of the strategies obtained after being processed in the IFE and EFE matrices are in Quadrant II. It states that the strategy used is a progressive strategy. This strategy means that the company has power but threats. Furthermore, in the QSPM analysis, the results were found that the main priority strategy that must be carried out is to build relationships with surrounding dayahs in an effort to expand marketing targets for dayah economic development in Bireuen district.